2017
DOI: 10.1002/lary.27009
|View full text |Cite
|
Sign up to set email alerts
|

The role of elective neck dissection in the treatment of maxillary sinus squamous cell carcinoma

Abstract: 4. Laryngoscope, 1835-1841, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 25 publications
(48 reference statements)
2
23
1
Order By: Relevance
“…Our occult node positivity rate of 12.7% aligns with previous studies that reported rates between 11.0% and 17.0%, with increasing propensity based on T‐classification 16 . We found that the rate of END performance in SNSCC increased significantly over time despite limited evidence supporting this practice, from 15.6% in 2004 to 31.3% in 2015.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our occult node positivity rate of 12.7% aligns with previous studies that reported rates between 11.0% and 17.0%, with increasing propensity based on T‐classification 16 . We found that the rate of END performance in SNSCC increased significantly over time despite limited evidence supporting this practice, from 15.6% in 2004 to 31.3% in 2015.…”
Section: Discussionsupporting
confidence: 89%
“…Previous analyses examining only the maxillary sinus subsite have reported mixed findings. For example, Sangal et al reported on a Surveillance, Epidemiology, and End Results (SEER) analysis of maxillary sinus SCC demonstrating a 5‐year overall and disease‐specific survival advantage with END for T3 tumors, but not for T1, T2, or T4 16 . Our analysis, in contrast, demonstrated no overall survival advantage in either T3 or T4 tumors.…”
Section: Discussioncontrasting
confidence: 48%
“…Sangal et al found conflicting results in a retrospective analysis of 927 patients with MS‐SCC with clinical N0M0 disease (Table ), 146 of whom underwent END . There was a statistically significant survival benefit in patients who received END with maxillectomy and adjuvant radiation therapy; however, in patients who did not receive adjuvant radiation therapy, END did not confer a survival benefit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recommendations were made using four retrospective cohort studies and one review (Level 3 evidence).…”
Section: Level Of Evidencementioning
confidence: 99%
See 1 more Smart Citation